Reticulocytes as marker of oxygen transport system adaption to physical activity in endurance sports - Rybina, I. (Baltic Journal of Sport and Health Sciences, 2015)
Backgraund. Peripheral blood reticulocytes and aging of the activity of these cells are markers of erythropoiesis activity. The purpose of this study was to examine changes of reticulocytes in blood formation of elite athletes in endurance sports during the preparation and the competitive periods. Methods. Reticulocytes and IRF content was examined in blood of 305 elite athletes aged 20-26 years that specialized in swimming, biathlon, cross-country skiing, kayaking and canoeing, rowing and cycling. At various stages of preparation 459 blood tests were performed and processed. Capillary blood was analysed using a haematology analyser SYSMEX XT 2000i. Results. Differences in reticulocytes depending on sport, gender and qualification were not found. Increase in reticulocytes was marked for male athletes in the age aspect, for females, reduction was observed. A tendency of average reticulocytes group data in peripheral blood at various stages of the annual preparation cycle was found: reduction of the amount of reticulocytes in competition period. This pattern was found regardless of gender. Similar evidence was found concerning the dynamics of IRF at the stages of the annual training. Conclusion. The effect of training activity on reticulocyte indices in the annual training cycle is related to the direction, duration and intensity of physical activity in different periods of training. Changes in reticulocytic indices may be due to effects such as hemoconcentration and hemodilution appearing after exercise in the corresponding areas of energy supply.